The philosopher's talk with the rhapsodist - Mejía Toro, Jorge Mario (Estudios de Filosofía, 1995)
By dividing the dialogue into a progressive series oflayers this paper attempts to place Ion within the cave of Plato's Politics with a view to gleaning maximum benefit from his juvenile shortcomings with the totalisation principie inherent to political thinklng, namely with "poetic" construction of a reflection-regulating space and which in Plato's works ís dubbed polis. As such, this demands a new reading of Plato's Politics as a work of art which proposes both in and through the possibility that it opens up, a new type of poetry, viz. philosophical poetry, which contrary to traditional poetry deemed to be valid in Plato's age, does not narrate facts, but rather creates them. The synthesis of this double movement leads us to posit three escape-routes from the vicious circle of violence: firstly, the theory of inspiration in Ion which prefigures the absence of myth, when in The Sophist Plato inverts his very own doctrine; secondly, poetry is that strange production which does not bear "something" from non-being to being; and thirdly, poetics is the protean totality that grafts -in thought- that which swarms and teethes when poetry is no longer seen as such a genre and yet is not quite another.